Propionic Acid Targets the TLR4/NF-κB Signaling Pathway and Inhibits LPS-Induced Intestinal Barrier Dysfunction: In Vitro and In Vivo Studies - Yang, Randong; Hu, Xiaoxiao; Xie, Xianzheng; Chen, Haiqiong; Fang, Huangyi; Zhu, Libing; Li, Zhongrong (Frontiers in Pharmacology, 2020)
Intestinal barrier dysfunction contributes to the development of intestinal diseases. Propionic acid (PA), a metabolite generated by anaerobic fermentation of dietary fiber in the intestinal cavity, has been proved to exert anti-inflammatory effects in a variety of diseases. However, the exact role of PA in LPS-induced intestinal barrier dysfunction is still unclear. Accordingly, we examined the latent mechanism of PA and its protective role in LPS-induced intestinal barrier dysfunction by both in vitro and in vivo experiments. In vitro, we identified that PA treatment could strongly promote cell migration, inhibit activation of NLRP3 inflammasome and maintain intestinal barrier function in LPS-induced IEC-6 cells, indicating the protective effect on the intestinal barrier function of PA. Further investigation of the mechanism involved revealed that PA could suppress the activation of TLR4/NF-κB pathway. In vivo, in a LPS-induced rat model, PA-induced protective effects in intestinal barrier dysfunction could be detected. In summary, our findings clarify the role of PA in intestinal barrier dysfunction and suggest that it is promising for the treatment of LPS-related intestinal diseases.